Role of Inferior Vena Cava Diameters as Predictor of Fluid Responsiveness in Mechanically Ventilated Pediatric Septic Shock - Khan, Momina; Sultana, Nighat; Parveen, Mahnaz; Muhammad, Saad; Sarwar, Muhammad (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the role of inferior vena cava diameters as predictor of fluid responsiveness in mechanically ventilated pediatric septic shock. Study Design: Prospective longitudinal study. Place and Duration of Study: Pediatric Intensive Care unit of The Children’s Hospital, Lahore Pakistan, from Nov 2023 to Apr 2024. Methodology: Utilizing non-probability consecutive sampling, patients with diagnosis of septic shock and on mechanical ventilation were selected from all PICU admissions. Inferior vena cava indices were measured using bedside ultrasound before and after one hour of fluid bolus. IVC diameter/BSA (body surface area) and IVC distensibility index (IVCDI) were calculated. Results: A total of 97 patients of both genders were included in the study, with a mean age of 9.00 (5.00 –13.00) years. The median of Minimal IVC diameter (cm) at 0-hour and after 1-hour were 0.43(0.31-0.50) and 0.45(0.34-0.56). Maximal IVC diameter (cm) at 0-hour and after 1-hour were 0.56(0.53-0.62) and 0.60(0.54-0.65) respectively. Highest sensitivity was noted for IVC-min/BSA at 1 hour with cut-off of <1.15 cm/m2. Highest negative predictive value was demonstrated for IVCDI at 1hr with cut-off value >15.86. 17% was taken as predictor of fluid responsiveness. Conclusion: Minimal IVC diameter and its distensibility index were found to be practical and noninvasive indicators of fluid responsiveness in pediatric septic shock, demonstrating feasibility at various time points from admission.